Footnotes to memory: exile, autobiography, and oblivion in four poets from Valparaiso (Galaz, Rodriguez, Mizon, and Embry) - Flores - Nibaldo Acero, Figueroa Ximena (Romanica Olomucensia, 2019)
From the selection of some of the most significant poems of Alicia Galaz, Osvaldo Rodriguez, Luis Mizon, and Eduardo Embry, all poets from Valparaiso and exiled from Chile during the military dictatorship of Pinochet, it is postulated that these poetics - written in Spanish and French - make up a meta-testimonial and autobiographical discourse of oblivion. For if the most recognized writings of this period are inclined to denounce the violence or the breakdown of identity caused by the dictatorship, these poets tend, instead, to create a poetic discourse about uprooting from a distance, based on the evocation of affectionate nostalgia that reconstructs the subjective memory of a full past in the province of origin and, in counterpoint, an impoverished present in the place of reception. It is, therefore, memorial and elegiac writings that atypically incorporate the experience of exile and, in addition, make visible a rare collective experience in the poetics of the time, which leads to them being considered in this work as part of an alternative "canon" of Chilean exile. In summary, these fragments can configure both an intimate memory and a common memory through an emotional historiography constituted by the pieces of a poet who also operates as an ethnographer and omniscient narrator of the facts and their desires.
Keywords: exile; memory; autobiography; forgetting; uprooting